2018
DOI: 10.4314/njbas.v25i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Possible Antidiabetic Mechanism of Action of Ex-maradi Okra Fruit Variety (<i>Abelmoscus esculentus</i>) on Alloxan Induced Diabetic Rats

Abstract: Increasing evidences suggest that postprandial hyperglycemia plays an important role in the development of diabetes complications. Therefore, therapeutic approaches that act via lowering of postprandial glucose leading to reduce insulin requirement are currently very attractive. The present study investigated some possible mechanisms of hypoglycemic action of different parts (Whole Okra "WO"; Okra Peel "OP" and Okra Seed "OS") of Ex-maradi Okra fruit variety in the management of diabetes mellitus in alloxan in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Different studies reported the effects of different parts of okra on alloxan-induced diabetic rats and showed that there was a significant reduction in the blood glucose level and glycated hemoglobin and an improvement in the lipid profile compared with the diabetic nontreated control rats and comparable with the metformin-positive control group [ 95 , 96 ]. Different parts of okra fruits can stimulate glycogen synthesis in the liver and delay the intestinal absorption of glucose in alloxan-induced diabetic rats [ 97 ]. In the same study, the histopathological examination of the pancreatic tissue after the administration of okra fruits revealed the evidence of pancreatic islet cell regeneration [ 97 ].…”
Section: In Vivo Studies On the Health Benefits Of Okra And Its Comentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies reported the effects of different parts of okra on alloxan-induced diabetic rats and showed that there was a significant reduction in the blood glucose level and glycated hemoglobin and an improvement in the lipid profile compared with the diabetic nontreated control rats and comparable with the metformin-positive control group [ 95 , 96 ]. Different parts of okra fruits can stimulate glycogen synthesis in the liver and delay the intestinal absorption of glucose in alloxan-induced diabetic rats [ 97 ]. In the same study, the histopathological examination of the pancreatic tissue after the administration of okra fruits revealed the evidence of pancreatic islet cell regeneration [ 97 ].…”
Section: In Vivo Studies On the Health Benefits Of Okra And Its Comentioning
confidence: 99%
“…Different parts of okra fruits can stimulate glycogen synthesis in the liver and delay the intestinal absorption of glucose in alloxan-induced diabetic rats [ 97 ]. In the same study, the histopathological examination of the pancreatic tissue after the administration of okra fruits revealed the evidence of pancreatic islet cell regeneration [ 97 ]. Okra supplementation statistically reduced the highlevels of fasting blood sugar, total cholesterol, and triglycerides and decreased the homeostasis model assessment of the basal insulin resistance index in diabetic rats, as reported by Majd et al (2018) [ 98 ].…”
Section: In Vivo Studies On the Health Benefits Of Okra And Its Comentioning
confidence: 99%
“…As reported in Table 1, some examples of current researches in animal models are moving in this direction [91,98,99,100,101,102].…”
Section: An Updated Overview Of Potential Beneficial Effects Assocmentioning
confidence: 99%
“…An interesting aspect was investigated by Muhammad et al [99] who studied the antidiabetic effects of different parts i.e., whole okra, okra peel, and okra seed of one of the varieties of okra ex-maradi in alloxan-induced diabetic rats: all parts of the okra fruits showed significant ( p < 0.05) reduction in blood glucose level, glycated hemoglobin, and improvement in lipid profile compared with the diabetic non treated control and comparable with metformin positive control [99]. A further work of the same authors proposed a possible mechanism of action of ex-maradi okra fruit variety ( Abelmoschus esculentus ) on alloxan-induced diabetic rats, by indicating that various parts of okra fruit have ability to stimulate glycogen synthesis in the liver and delay intestinal absorption of glucose with very significant glucose dialysis retardation index and high glucose adsorption capacity [100]. Moreover, the authors reported how histological examination of the pancreatic tissue after administration of okra fruit revealed evidence of pancreatic islets cells regeneration [100].…”
Section: An Updated Overview Of Potential Beneficial Effects Assocmentioning
confidence: 99%
See 1 more Smart Citation